Reactive Oxygen Species Tune Root Tropic Responses . Issue 2 (17th August 2016) - Krieger, Gat; Shkolnik, Doron; Miller, Gad; Fromm, Hillel
Abstract : ROS accelerates gravitropism but attenuates hydrotropism of Arabidopsis roots. Abstract: The default growth pattern of primary roots of land plants is directed by gravity. However, roots possess the ability to sense and respond directionally to other chemical and physical stimuli, separately and in combination. Therefore, these root tropic responses must be antagonistic to gravitropism. The role of reactive oxygen species (ROS ) in gravitropism of maize and Arabidopsis ( Arabidopsis thaliana ) roots has been previously described. However, which cellular signals underlie the integration of the different environmental stimuli, which lead to an appropriate root tropic response, is currently unknown. In gravity-responding roots, we observed, by applying the ROS -sensitive fluorescent dye dihydrorhodamine-123 and confocal microscopy, a transient asymmetric ROS distribution, higher at the concave side of the root. The asymmetry, detected at the distal elongation zone, was built in the first 2 h of the gravitropic response and dissipated after another 2 h. In contrast, hydrotropically responding roots show no transient asymmetric distribution of ROS . Decreasing ROS levels by applying the antioxidant ascorbate, or the ROS -generation inhibitor diphenylene iodonium attenuated gravitropism while enhancing hydrotropism. Arabidopsis mutants deficient in Ascorbate Peroxidase 1 showed attenuated hydrotropic root bending. Mutants of the root-expressed NADPH oxidase RBOH C, but not rbohD, showed enhanced hydrotropism and less ROS in their roots apices (tested in tissue extracts with Amplex Red). Finally, hydrostimulation prior to gravistimulation attenuated the gravistimulated asymmetric ROS and auxin signals that are required for gravity-directed curvature. We suggest that ROS, presumably H2 O2, function in tuning root tropic responses by promoting gravitropism and negatively regulating hydrotropism.